Development of student worksheets material on biodiversity of Tidung tribe medicinal plants in SMA Negeri 3 Nunukan - Agus Annisah; Atok Miftachul Hudha; S. Sukarsono; Abdulkadir Rahardjanto; Eko Susetyarini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Local wisdom in the use of medicinal plants is still not understood by students' potential. This study aims to develop student worksheets (LKPD) on biodiversity of medicinal plants of the tidung tribe for class X students at SMA Negeri 3 Nunukan Regency. The research method used is Research and Development (R&D) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The population included 93 students, with a sample of 25 students. This research involved two types of tests, namely feasibility test and practicality test. The feasibility test was conducted by material experts, media experts, linguists, and practitioners, while the practicality test was conducted by teachers and students. The results showed that the feasibility test obtained the following percentages: material experts 93.5% (very feasible), media experts 84.75% (feasible), linguists 96.5% (very feasible), and practitioners 97.91% (very feasible). Based on the results of the analysis, it can be concluded that the LKPD based on the local wisdom of the tidung tribe on medicinal plant biodiversity material is declared very feasible and very practical to be used in learning. The integration of local wisdom in this LKPD is proven to be effective in increasing interest in learning, understanding the concept of biodiversity, and students' awareness of the preservation of local culture. This research is expected to be a reference in the development of local wisdom-based learning tools for other subjects.